Mathematics
copperhead2236
53

how would you do this problem (7t-2)-(-3t+1)=-3(1-3t)?

+5
(2) Answers
Genna57

yo hs to distribute (7t-2)-1(-3t+1)=-3(1-3t) 7t-2+3t-1=-3+9t 7t+3t-2-1=-3+9t add like terms 10t-3=9t-3 add 3 both sides 10t=9t minus 9t from both sides t=0

ayannachhokar

(7t-2)-(-3t+1)=-3(1-3t) I would distribute everything for the first step, this gives you 7t-2+3t-1 = -3+6t Next, combine like terms. 10t-3 = -3+6t Put the variable on one side. 10t-3 = -3+6t - 6t           -6t 4t-3 = -3 Get the variable alone 4t-3 = -3    +3   +3 4t = 0 4t/4 = 0/4 t = 0

Add answer